2021
DOI: 10.1016/j.bonr.2021.101114
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphatase 1 regulatory subunit 18 suppresses the transcriptional activity of NFATc1 via regulation of c-fos

Abstract: The transcription factor NFATc1 and its binding partner AP-1 (a complex containing c-fos and c-Jun) play a central role in osteoclast differentiation. NFATc1 and AP-1 promote the expression of target genes such as Acp5, Ctsk and also auto-regulate NFATc1 expression as well. We previously reported that protein phosphatase 1 regulatory subunit 18 (PPP1r18) is a negative regulator of osteoclast bone resorption by inhibiting cell attachment to bone matrix. We also repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…PPP1r18 expression is considerably reduced during osteoclast differentiation, similar to Cbp levels in osteoclasts and other tissues. In addition, PPP1r18 negatively regulates NFATc1 transactivation by destabilizing c-Fos, which is a complex partner of NFATc1 [ 9 ]. NFATc1 and c-fos are upregulated in lymphoid cells during inflammation as they promote the differentiation and function of immune cells, such as T and B cells [ 44 , 45 ].…”
Section: Regulation Of Src Activity In Osteoclastsmentioning
confidence: 99%
See 1 more Smart Citation
“…PPP1r18 expression is considerably reduced during osteoclast differentiation, similar to Cbp levels in osteoclasts and other tissues. In addition, PPP1r18 negatively regulates NFATc1 transactivation by destabilizing c-Fos, which is a complex partner of NFATc1 [ 9 ]. NFATc1 and c-fos are upregulated in lymphoid cells during inflammation as they promote the differentiation and function of immune cells, such as T and B cells [ 44 , 45 ].…”
Section: Regulation Of Src Activity In Osteoclastsmentioning
confidence: 99%
“…Osteoclasts differentiate from hematopoietic stem cells upon stimulation with macrophage colony-stimulating factor (M-CSF) and receptor activator of nuclear factor kappa-B ligand (RANKL), which are secreted by osteoblasts [ 5 , 6 ]. RANKL binds to the receptor activator of nuclear factor kappa-B (RANK) and activates nuclear factor kappa-B (NF-κB) and mitogen-activated protein kinase (MAPK) signaling [ 5 , 7 , 8 , 9 ]. The AP-1 complex consists of c-Jun and c-fos under the MAPK signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer, the majority of which is adenocarcinoma, ranks fifth in cancer incidence and is the fourth leading cause of cancer-related mortality globally, with about 1,089,000 new cases and around 769,000 associated deaths in 2020 [ 1 - 4 ]. While resection remains the mainstay and cornerstone of curative treatment for most non-metastatic gastric adenocarcinoma (nmGaC) [ 5 , 6 ], increasing numbers of patients with nmGaC also receive chemotherapy, based on evidence from major clinical trials [ 7 - 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…By means of TCGA data mining, protein phosphatase 1 regulatory subunit 18 (PPP1R18) was finally identified by us in KIRC, after a series of gene filtrations including difference analysis, survival analysis, univariate analysis, multivariate analysis, other datasets and polymerase chain reaction (PCR) validations, sequentially. To our knowledge, PPP1R18, also known as HKMT1098, KIAA1949, was reported to be a protein phosphatase 1 (PP1)-binding protein, or an actin-regulatory protein [ 6 , 7 ]. Matsubara et al revealed that PPP1R18 was able to regulate osteoclasts’ bone resorption activity, maturation and actin ring formation [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Matsubara et al revealed that PPP1R18 was able to regulate osteoclasts’ bone resorption activity, maturation and actin ring formation [ 6 ]. Yasuda et al shed light on that PPP1R18 could suppress the transcriptional activity of NFATc1 to repress osteoclast differentiation at early stage [ 7 ]. As for cancer research, Ha et al identified eight differentially expressed genes above 16-fold changes including PPP1R18, that were significantly related to preoperative chemoradiation therapy responses in rectal cancer [ 8 ].…”
Section: Introductionmentioning
confidence: 99%